Pengaruh Pemberian Latihan Otot Panggul untuk Mengurangi Frekuensi Inkontinensia Urine pada Wanita Lansia - Pradita Setianingrum; Nella Vallen; Kristina Maharani (Corona: Jurnal Ilmu Kesehatan Umum, Psikolog, Keperawatan dan Kebidanan, 2025)
Urinary incontinence is a common medical condition among older women, characterized by the involuntary leakage of urine due to impaired bladder control. This condition not only affects physical health but also has significant psychosocial impacts, including reduced self-confidence and quality of life. Non-pharmacological interventions, particularly pelvic floor muscle exercises, have been recognized as effective strategies to strengthen the bladder sphincter and pelvic floor muscles, thereby enhancing urinary retention. The present study aimed to evaluate the effectiveness of pelvic floor muscle exercises in reducing the frequency of urinary incontinence among elderly women. An experimental design with a one-group pretest–posttest approach was employed. The study population consisted of 64 elderly women receiving care at the Gunung Pati Public Health Center in Semarang, from which 45 participants were selected through purposive sampling based on inclusion criteria. Data were collected using structured questionnaires and clinical observation to assess the frequency of urinary incontinence episodes before and after the intervention. Statistical analysis was performed using the Wilcoxon signed-rank test, and the results indicated a significant reduction in urinary incontinence episodes following the exercise program, with a p-value of <0.001. These findings suggest that pelvic floor muscle exercises are a simple, cost-effective, and non-invasive intervention to manage urinary incontinence in elderly women. Implementing such exercises in community health programs can play a vital role in promoting the well-being and independence of older women. The study recommends incorporating pelvic floor muscle training into routine elderly care services and encourages further research with larger samples and longer follow-up periods to confirm the long-term benefits.